2019
DOI: 10.1002/berj.3586
|View full text |Cite
|
Sign up to set email alerts
|

A two‐level study of predictors of private tutoring attendance at the beginning of secondary schooling in Germany: The role of individual learning support in the classroom

Abstract: More and more students attend private supplementary tutoring to improve their academic achievement. Private tutoring might be understood as a reaction to insufficient instructional quality in school, especially regarding individual support. However, it might also be possible that parents generally see insufficient grades as an indicator of lacking support and engage a tutor in hopes of improvement or to enhance a competitive edge for their children. So far, the relationship between tutoring attendance and perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Research has shown that private tutoring has become a commercial market and family cost (Yung & Chiu, 2020;, gaining global prevalence from East Asia to all parts of the world (Bray, 2013;Byun et al, 2018;Guill et al, 2020). These reasons agree with what was said by Zhang and Bray.…”
Section: Introductionsupporting
confidence: 79%
“…Research has shown that private tutoring has become a commercial market and family cost (Yung & Chiu, 2020;, gaining global prevalence from East Asia to all parts of the world (Bray, 2013;Byun et al, 2018;Guill et al, 2020). These reasons agree with what was said by Zhang and Bray.…”
Section: Introductionsupporting
confidence: 79%
“…The style of teaching also matters. Guill, Lüdtke, and Schwanenberg (2020) showed, for Germany, that a more individualised support for students in the classroom reduces the probability of participation in private tutoring in English.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rather than providing an exhaustive list of factors that may or may not influence students' goals and experienced benefits (cf. Guill, Lüdtke, & Schwanenberg, 2019;Yung & Chiu, 2020), in this section, we examine what students' goals and experienced benefits can be, and how such goals and benefits are indicative of interrelationships between institutions (Figure 1).…”
Section: Conceptual Frameworkmentioning
confidence: 99%